Fundamentals of C++ - Kenneth, Alfred Lambert (Course Technology/Thomson Learning, 2001)
Following the success of Fundamentals of C++ by Lambert and Nance, C++ Introductory course is essential for a first course in Computer Science. Completely updated, this text provides in-depth coverage to help students prepare for the AP exam, Exam A. A full introduction to the essential features of C++ is provided and programming techniques are emphasized in the context of interesting and realistic case problems. This text is compatible with C++ compilers from Microsoft, Borland, and Metrowerks